2012
DOI: 10.1103/physrevb.86.081301
|View full text |Cite|
|
Sign up to set email alerts
|

Robust optical emission polarization in MoS2monolayers through selective valley excitation

Abstract: We report polarization resolved photoluminescence from monolayer MoS2, a two-dimensional, non-centrosymmetric crystal with direct energy gaps at two different valleys in momentum space. The inherent chiral optical selectivity allows exciting one of these valleys and close to 90% polarized emission at 4K is observed with 40% polarization remaining at 300K. The high polarization degree of the emission remains unchanged in transverse magnetic fields up to 9T indicating robust, selective valley excitation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
315
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 424 publications
(335 citation statements)
references
References 25 publications
15
315
2
3
Order By: Relevance
“…Our experimental observations also rule out a spin-Zeeman contribution to the measured splitting. In fact, the strong spin-orbit interaction in both the conduction and valence band of WSe 2 (refs 24,25) ensures that the spin degree of freedom is frozen out and does not contribute to the B-induced splitting, which is consistent with earlier studies that reported insensitivity of circular dichroism to an in-plane magnetic field 4,26 .…”
supporting
confidence: 80%
“…Our experimental observations also rule out a spin-Zeeman contribution to the measured splitting. In fact, the strong spin-orbit interaction in both the conduction and valence band of WSe 2 (refs 24,25) ensures that the spin degree of freedom is frozen out and does not contribute to the B-induced splitting, which is consistent with earlier studies that reported insensitivity of circular dichroism to an in-plane magnetic field 4,26 .…”
supporting
confidence: 80%
“…96.201113 Introduction. The last few years have witnessed an explosion in research on monolayer transition metal dichalcogenides (TMDCs) driven mainly by their unique optical properties [1][2][3][4][5][6][7][8]. In contrast to their bulk counterparts, the monolayer TMDCs possess a direct band gap [9,10] leading to very strong light-matter interactions.…”
Section: Dark Excitations In Monolayer Transition Metal Dichalcogenidesmentioning
confidence: 99%
“…Here, we benefit from the chiral optical selection rules in TMDC monolayers, which allow optical excitation in the K þ or K − valley, using σ þ or σ − polarized laser excitation, respectively [26,30,[76][77][78]; see scheme in Fig. 3(a).…”
Section: Valley Polarization and Valley Coherence Manipulationmentioning
confidence: 99%